2013
DOI: 10.1194/jlr.r036095
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the complexities of the HDL lipidome

Abstract: This article is available online at http://www.jlr.org For many years, HDL lipids were predominantly characterized in terms of the content of their major classes, notably phospholipids, unesterifi ed (free) sterols (predominantly cholesterol), cholesteryl esters, and triglycerides. Cholesterol is the most characteristic component of the HDL lipidome as, in the form of HDL-cholesterol, it represents a major independent negative risk factor for cardiovascular disease (see other reviews in this Thematic Series). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
254
1
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 310 publications
(270 citation statements)
references
References 143 publications
10
254
1
5
Order By: Relevance
“…Some of these assays may be amenable to routine diagnostic testing and relate to HDL function, and hence CVD risk. The best example of this is the use of nuclear magnetic resonance (NMR) spectroscopy for measuring HDL particle number, which has been shown in several large studies to be superior to HDL-C in predicting future cardiovascular events (4,183,184 ). NMR can also be used to quantify specific HDL subfractions, such as apoB-containing lipoproteins, as well as LDL and HDL particle size and distribution, which may also be predictive of increased mortality in a wide range of disease states (185)(186)(187)(188)(189)(190).…”
Section: Hdl Assays Based On Physical Propertiesmentioning
confidence: 99%
“…Some of these assays may be amenable to routine diagnostic testing and relate to HDL function, and hence CVD risk. The best example of this is the use of nuclear magnetic resonance (NMR) spectroscopy for measuring HDL particle number, which has been shown in several large studies to be superior to HDL-C in predicting future cardiovascular events (4,183,184 ). NMR can also be used to quantify specific HDL subfractions, such as apoB-containing lipoproteins, as well as LDL and HDL particle size and distribution, which may also be predictive of increased mortality in a wide range of disease states (185)(186)(187)(188)(189)(190).…”
Section: Hdl Assays Based On Physical Propertiesmentioning
confidence: 99%
“…219 The phospholipid content and composition have a strong effect on the size, shape, fluidity, and surface charge of HDLs. 28 Their contribution to the functionality of HDLs has been tested experimentally by reconstituting artificial HDL particles with defined phosphatidylcholine species at different concentrations. Increased concentrations of phosphatidylcholine increase the ability of HDLs to induce SR-BI-mediated cholesterol efflux.…”
Section: Post-translational Modifications Of Proteinsmentioning
confidence: 99%
“…19 Hence, it is assumed that the cardioprotective effects of HDL are largely based on its ability to remove cholesterol from macrophages, which represents the first and crucial step of reverse cholesterol transport. 20 In recent years, it has become evident that the atheroprotective, anti-inflammatory, and antioxidative effects of HDL are critically dependent on its protein cargo [21][22][23][24] because HDLassociated proteins were found to be involved in many biologic functions apart from lipid metabolism, such as regulation of inflammation and immune responsiveness. 15 We and others have shown that qualitative alterations of HDL in CKD and ESRD result in dysfunctional properties, transforming HDL from a protective to a deleterious particle.…”
mentioning
confidence: 99%